A mathematical model for cost budget optimization in the early stage of house construction budget analysis. Issue 3 (3rd April 2022) - Malathi, S.; Kumar, Ankit; Venkatesan, R.; Sundar, Naveen; Athigiri Arulalan, A. S.; Ambeth Kumar, V. D.; Priya, R.; Sharma, Shilpa; Raja, Linesh
Abstract: House building is a desire for many individuals these days. If we create our own structure via our own efforts, we may save money to a certain amount, but this is not feasible for everyone, particularly for families with two employees. Because the employee's family cannot devote their entire attention to all areas of the building as and when necessary, they naturally present material contracts and negotiate with the builders. The length and cost of a prefabricated construction project are converted into quantifiable cost data during the early stages of the project using an earned value analysis technique, which is then used to determine the project's implementation cost. A mathematical model of the pre-cost budget for prefabricated buildings is built based on the project parameters. By comparing the improved neural network algorithm's cost budget performance in the early stages of an assembly construction project to that of the original mathematical model, it was determined that the improved neural network algorithm's cost budget performance was superior, and the cost budget performance was improved. Methodology: first plan the preparation of the house construction, then determine whether the location is urban or rural, then calculate the square footage and floor division for their convenience, as well as check quantity take off, evaluate the primary materials for house construction, and paint the entire house, as well as fix rooms doors, windows, and window grilles. Following the selection of floor laying stones, the budget will be computed. Result and conclusion: I concluded that home building estimation is beneficial for newly constructed individuals, and then this project thoroughly taught how to calculate the house construction budget and how to implement it within our budget.